Kolaborasi Antara Pt Gas Negara Dengan Pemerintah Kota Yogyakarta Dalam Mewujudkan Smart City - Kurniasari, Lenny; Purnomo, Eko Priyo; Salsabila, Lubna (Jurnal Noken: Ilmu-Ilmu Sosial, 2020)
This study aims to describe the form of collaborative governance between the Government of Yogyakarta City and the business sector, namely PT Gas Negara in realizing smart cities. The focus of this research is to describe the process of cooperation between the two parties (Government and Private) so that a memorandum of understanding is created to support smart city. This study uses the cross-sector collaboration theory of John M Bryson and Barbara C. Crosby who mentioned collaborative governance must pay attention to the process. This study uses a qualitative patterned research method, while the data from this study are obtained through participant observation, in-depth interviews, document analysis, media and literature. Data in this study were analyzed using data triangulation techniques. Following are some of the findings from this study. First, PT Perusahaan Gas Negara Tbk signed a memorandum of understanding with the Yogyakarta City Government in supporting the smart city program by providing infrastructure and utilizing natural gas as an alternative energy source. Second, PT PGN developed the PGN 360 Degree Integrated Solution service as a follow-up to the provision of electronic-based services and thirdly, the Yogyakarta City Government utilized the ICT services / provider of optical fiber networks owned by PT PGN as a support for smart cities.